Cause of amblyopia in adult patients: a cross-sectional study - Waheed, Abdul; Kumari, Nitika; Ali, Jamshed; Dubey, Gaurav; Kumari, Vibha; Kumari, Ragni; Shahid, Yasmeen (International Journal Of Community Medicine And Public Health, 2021)
Background: Amblyopia has been defined as a decrease of visual acuity for which no causes can be detected by the physical examination of the eye, caused by vision deprivation or abnormal binocular interaction. This study aims to determine the cause of amblyopia in adult patients at HAHC hospital South Delhi. Methods: This is a cross-sectional study conducted over a period from January 2018 till March 2018 among the patients in HAHC hospital. A comprehensive eye examination was used to analyse the visual condition. Results: Amblyopia was diagnosed in 42 participants, with age-and gender-adjusted prevalence of 3.2%. Of these, 1.9% were unilateral cases, and 1.3% were bilateral cases. A major cause of amblyopia in this population was a refractive error, hence using spectacle correction and vision therapy for its initial management. Conclusions: This study has provided causes of amblyopia in an adult population. Amblyopia is a frequent cause of lifelong unilateral visual impairment.